Optimisation Of Mixed Drink Made From Red Cabbage (Brassica oleracea L.) And Roselle (Hibiscus sabdariffa L.) Extracts - Nur Farah Hani, M.; Hafiza, Y.; Faridah, H.; Nur Huda Faujan; Norlelawati Arifin (Malaysian Applied Biology Journal, 2024)
Indexed by Scopus/MyCite